Sedasi dan Analgesia di Ruang Rawat Intensif - Sudjud, Reza Widianto; , Indriasari; Yulriyanita, Berlian (Perdatin Pusat, 2014)
Pasien sakit kritis, khususnya yang mendapatkan ventilasi mekanik, seringkali mengalami nyeri dan kecemasan. Prinsip utama dari perawatan di ruang rawat intensif (ICU) adalah memberikan rasa nyaman sehingga pasien dapat mentoleransi lingkungan ICU yang tidak bersahabat. Pengelolaan sedasi dan analgesia yang adekuat dapat mempersingkat penggunaan ventilasi mekanik dan lama perawatan di ICU. Hal ini dapat dilakukan dengan mengidentifikasi dan mengatasi penyakit dasar dan faktor pencetus, menggunakan metode nonfarmakologi untuk meningkatkan rasa nyaman, pemberian terapi sedasi dan analgesia dengan memilih obat yang tepat, serta pemantauan secara rutin untuk menghindari terapi yang berlebihan dan berkepanjangan. Kata kunci: Analgesia, cemas, nyeri, ruang rawat intensif, sedasi Critically ill patients, especially those who receive mechanical ventilation, oftenexperience pain and anxiety. The main principle of treatment in the intensive care unit (ICU) is to provide a sense of comfort so that the patient can tolerate the ICU environment.Management of adequate sedation and analgesia can shorten the use of mechanical ventilation and length of ICU care. This can be done by identifying and correcting the underlying disease and precipitating factors, use of non-pharmacological methods to improve comfort, sedation and analgesia therapy with choosing the right drug, as well as regular monitoring to avoid excessive and prolonged therapy. Key words: Analgesia, anxiety, intensive care unit, pain, sedation Reference Rathmell.P.James. Bonica’s Management of Pain. Pain management in the intensive care unit. Lippincott Williams 2012;112:1590–01. Sessler CN, Wilhem W. Analgesia and sedation in the intensive care unit: an overview of the issues Crit Care. 2008;12(Suppl 3): S1. Young J. Sedation. Dalam: Core topics in critical care medicine. New York: Cambridge university press; 2010:77–88. Singer M WAR. Oxford handbook of critical care. Pain and post operative intensive care. Oxford University Press Inc; 2005:530–35. Marino P L. The ICU book: Analgesia and Sedation. Lippincott williams & wilkins; 2007;49:938–66. McConachie I. Handbook of ICU therapy. Analgesia for the high risk patient. New York: Cambridge University Press; 2006;4:51–64. Sessler CN VK. Patient-Focused Sedation and Analgesia in The ICU. Chest 2008;133:552–65. Mitchell E. Pain control. Dalam : Core topics in critical care medicine. New York: Cambridge university press; 2010:72–6. Peitz J Gregory, Olsen M Keith. Top 10 Myths Regarding Sedation and Delirium in the ICU. J Critical Care Medicine 2013;41:S46–56. Reade C Michael, Finfer Simon. Sedation and Delirium in the Intensive Care Unit. J New England 2014:444–54. Riessen.R, Pech.R. Comparison of the ramsay score and the richmond agitation sedation score for the measurement of sedation depth. Crit Care 2012.16 (Suppl 1):326. Recommended standards for short latency auditory evoked potentials.American clinical neurophysiology society.2008:12-9. Stern. TA. Manual of intensive care medicine. Diagnosis and treatment of agitation and delirium in the intensive care unit patient. Lippincott williams.2000; 179:871–75.